The Role and Impact of Salivary Zn Levels on Dental Caries - Milaim Sejdini; Agim Begzati; Sami Salihu; Sokol Krasniqi; Nora Berisha; Nora Aliu (Hindawi Limited, 2018)
Introduction. Minimal attention has been given to the role of salivary microelements, the importance they have in reducing the intensity of caries, and the effect of caries prophylaxes. Aim. This research aimed to determine the concentration and quantity of Zn and its impact on the prevention and the reduction of the intensity of caries in schoolchildren aged 12-13 years with permanent dentition. Methods. For this research, we analyzed the stimulated and nonstimulated full saliva of 106 schoolchildren divided into three groups by mean decayed, missing, and filled teeth (DMFT) index. The control group consisted of 25 caries-free children, the second group had 47 children with mean DMFT index of 1 to 6, and the third group had 34 children with DMFT index of ≥ 6. Complete saliva was collected from all children in a sterile test tube. Results. The concentration of Zn in saliva before stimulation in caries-free children has variations of the order of 0.001+ to 0.01 mmol/l. The maximum concentration after stimulation is 6.72 mmol/l, while the maximum value is 64.38 mmol/l. Conclusion. The Zn concentration in the stimulated saliva showed a significant increase in the group of caries-free children and could be described as a positive value for the reduction of caries.